Increased hepatic fibrosis and JNK2-dependent liver injury in mice exhibiting hepatocyte-specific deletion of cFLIP - Schattenberg, Jörn Markus; Longerich, Thomas (American journal of physiology. Gastrointestinal and liver physiology, 2012)
Chronic liver disease promotes hepatocellular injury involving apoptosis and triggers compensatory regeneration that leads to the activation of quiescent stellate cells in the liver. The deposition of extracellular matrix from activated myofibroblasts promotes hepatic fibrosis and the progression to cirrhosis with deleterious effects on liver physiology. The role of apoptosis signaling pathways in the development of fibrosis remains undefined. The aim of the current study was to determine the involvement of the caspase-8 homologue cellular FLICE-inhibitory protein (cFLIP) during the initiation and progression of fibrosis. Liver injury and fibrosis from carbon tetrachloride (CCl(4)) and thioacetamide (TAA) were examined in mice exhibiting a hepatocyte-specific deletion of cFLIP (flip(-/-)). Acute liver injury from CCl(4) and TAA were enhanced in flip(-/-) mice. This was accompanied by increased activation of caspase-3 and -9, pronounced phosphorylation of JNK, and decreased phosphorylation of Erk. Deletion of the cJun NH(2)-terminal kinase 2 (JNK2) in flip(-/-) mice protected from injury. Hepatic fibrosis was increased at baseline in 12-wk-old flip(-/-) mice, and progression of fibrosis from TAA was accelerated compared with the wild type. In conclusion, deletion of cFLIP in hepatocytes leads to increased fibrosis and accelerated fibrosis progression. This is accompanied by increased injury involving the activation of caspases and JNK2. Thus predisposition to liver injury involving increased hepatocellular apoptosis is a critical mediator of accelerated fibrogenesis, and prevention of liver injury will be a most important measure for patients with chronic liver disease.